#### notes

In the previous class you have studied that if value of the polynomial is zero for

x = a then (x - a) is a factor of that polynomial. That is if p(x) is a polynomial and p(a) = 0 then (x - a) is a factor of p(x). In this case ’a’ is the root or solution of p(x) = 0

For Example

Let x = -6 in the polynomial x^{2} + 5x - 6

x^{2} + 5x - 6 = (-6)2 + 5 × (-6) - 6

= 36 - 30 - 6 = 0

∴x= -6 is a solution of the equation.

Hence -6 is one root of the equation

x^{2} + 5x - 6 = 0

Let x = 2 in polynomial x2 + 5x - 6

x^{2} + 5x - 6 = 22 + 5×2 - 6

= 4 + 10 - 6

= 8 ¹ 0

∴ x = 2 is not a solution of the

equation x^{2} + 5x - 6 = 0